Platform developmentalism: Leveraging platform innovation for national development in Latin America - Katherine Reilly (Internet Policy Review, 2020)
Recently, development scholars have begun to study the platform economy. In Latin America, platformisation has resulted in the widespread reorganisation of business practices across many sectors, with important implications for incumbent industries, labour and social processes. These changes raise questions about the potential contributions of platformisation to national economic health and social welfare. This paper argues that the link between platformisation and development can be studied from a developmental state point of view. Specifically, in Latin America, the disruptions caused by platform innovations create policy windows that could result in platform developmental policy innovations, however, developmental policy-making is constrained by the structural characteristics of Latin American economies. Taking this into consideration, the paper positions Biber et al.'s (2017) model of policy disruption, and Fairfield's (2015) model of policy influence as tools to critically assess platform policymaking from a developmentalist point of view. This approach is illustrated through a survey and discussion of policy disruptions caused by platformisation in the transportation, lodging and fintech sectors of Chile, Colombia, Mexico and Peru. The discussion surfaces specific challenges for platform developmentalism related to policy autonomy and capture, societal mobilisation of data and other resources, and state-market collaborations. The paper concludes by positioning the "platform society" as a normative goal and offers an agenda to advance it through comparative research of platform policymaking.
Keywords: 300; Platform economy; Policy disruption; Developmentalism; Latin America; Platforms